2016
DOI: 10.1099/ijsem.0.001238
|View full text |Cite
|
Sign up to set email alerts
|

Flexivirga lutea sp. nov., isolated from the faeces of a crested ibis, Nipponia nippon, and emended description of the genus Flexivirga

Abstract: Flexivirga lutea sp. nov., isolated from the faeces of a crested ibis, Nipponia nippon, and emended description of the genus Flexivirga , was isolated from the faeces of a crested ibis, Nipponia nippon. The phylogenetic analysis based on the 16S rRNA gene sequences showed that the closest relative of TBS-100T was Flexivirga alba DSM 24460 T with 97.11 % sequence similarity, and that strain TBS-100 T belonged to the genus Flexivirga. The optimum growth conditions for strain TBS-100 T were 30 C, at a pH of 7 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Genomic ANI and dDDH analyses, together with physiological and biochemical analyses, confirmed that strain Q11 T is a novel species of the genus Flexivirga. Compared with the reported strains of the genus Flexivirga [1][2][3][4][5][6], strain Q11 T has the abilities of nitrogen fixation (181.80 IU/L), IAA production (3.26 mg/L in 2 days), and plant growth promotion, this last function being described for the first time for the genus Flexivirga. Previous research showed that endophytes promote plant growth through nitrogen fixation, phosphorus dissolution, and growth hormone production [12,79].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Genomic ANI and dDDH analyses, together with physiological and biochemical analyses, confirmed that strain Q11 T is a novel species of the genus Flexivirga. Compared with the reported strains of the genus Flexivirga [1][2][3][4][5][6], strain Q11 T has the abilities of nitrogen fixation (181.80 IU/L), IAA production (3.26 mg/L in 2 days), and plant growth promotion, this last function being described for the first time for the genus Flexivirga. Previous research showed that endophytes promote plant growth through nitrogen fixation, phosphorus dissolution, and growth hormone production [12,79].…”
Section: Discussionmentioning
confidence: 85%
“…The genus Flexivirga, a member of the Phylum Actinobacteria, was first described by Anzai et al [1]. The List of Prokaryotic Names with Standing in Nomenclature (https://lp sn.dsmz.de/search?word=Flexivirga, accessed on 8 October 2023) contains six species with legitimately recognized names, i.e., Flexivirga alba [1], Flexivirga endophytica [2], Flexivirga lutea [3], Flexivirga oryzae [4], Flexivirga caeni [5], and Flexivirga aerilata [6], which were isolated from the leaves of basil [2], the feces of ibis [3], the soil of a rice paddy [4], activated sludge [5], and an automobile air conditioning system [6], respectively. All members of the genus Flexivirga are described as Gram-positive bacteria, aerobic, non-motile, and with a high G + C content in their DNA (~67 mol%).…”
Section: Introductionmentioning
confidence: 99%